Meningkatkan Keterlibatan Siswa melalui Market Place Activity (MPA) dalam Pembelajaran Sejarah Kebudayaan Islam - Hasna Whidia; Mawi Khusni Albar (Lembaga Yasin AlSys, 2026)
Studies on the application of the Market Place Activity (MPA) model in teaching Islamic Cultural History (SKI) at the Madrasah Aliyah level remain limited, as does in-depth exploration of students’ responses to this model in the context of Islamic history. This study aims to analyze the process of implementing the MPA model at MAN 2 Kebumen and its impact on the cognitive, affective, and conative dimensions of students’ responses. This study employed a descriptive qualitative approach involving the SKI teacher, the vice principal for curriculum, and students selected through purposive sampling. Data were collected through participant observation, in-depth interviews, and documentation. The results showed that the implementation of the MPA model was carried out systematically through the stages of planning, implementation, and evaluation. This model helped students master the material in the cognitive dimension, increased enthusiasm and communication skills in the affective dimension, and demonstrated the effectiveness of process evaluation through non-test techniques in monitoring student engagement and oral mastery of the material, although the aspect of written assessment still requires optimization. These findings indicate that the MPA model is a strategic alternative for modernizing SKI instruction, which has thus far been dominated by the lecture method, while also providing a theoretical contribution to the development of Islamic pedagogy literature and practical implications for educational institutions in strengthening more active history learning.